A T 1 MRI detectable hyaluronic acid hydrogel for in vivo tracking after intracerebral injection in stroke - Said, Moustoifa; Jing, Jing; Montigon, Olivier; Collomb, Nora; Vossier, Frédérique; Chovelon, Benoît; El Amine, Bayan; Jeacomine, Isabelle; Lemasson, Benjamin; Barbier, Emmanuel Luc; Detante, Olivier; Rome, Claire; et al. (Journal of materials chemistry. B, Materials for biology and medicine, 2025)
Injectable hydrogels have emerged as a promising strategy for treating stroke and neurodegenerative diseases, but their effectiveness depends on precise injection, defect filling, and long-term retention at the target site. While MRI can help visualize hydrogels, distinguishing them from fluid-filled spaces, like a post-stroke cavity at a chronic stage, is challenging owing to their high water content and similar MR properties. In this study, a MRI detectable hyaluronic acid (HA) hydrogel that is injectable and self-healing was developed for tracking after intracerebral injection in stroke. This HA hydrogel was functionalized with a thermodynamically stable and kinetically inert gadolinium(III) complex for monitoring its long-term fate in the brain with -contrast enhanced MRI. The dynamic covalent cross-links based on boronate ester bonds in the hydrogel network ensured precise injection and instantaneous self-healing. The HA network did not induce adverse tissue response and was biocompatible with therapeutic cells (human adipose stromal/stem cells). Furthermore, this labeling strategy enabled accurate tracking of hydrogel distribution and degradation in stroke condition, allowing a better assessment of efficacy and safety. This MRI-visible hydrogel has significant potential as a scaffold for stem cells, growth factors, and/or drugs, paving the way for more effective treatments for brain disorders.